MELACAK TRADISI AL-A’MĀL AL-YAUMIYYAH MASYAYIKH PONDOK PESANTREN ANNUQAYAH GULUK-GULUK SUMENEP - Faris Ahmad Toyyib; M. Mushthafa (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
The existence of al-a'māl al-yaumiyyah is one of the main parts of pesantren education. It can be seen as a perfect representation of pesantren education: cultivating knowledge, moral discipline, and spiritual discernment. Historically, the al-a'māl al-yaumiyyah tradition cannot be separated from the network between kiai, both in the nusantara and with Islamic centers in various countries, especially in Arab countries. This paper aims to reveal two things; first, what al-a'māl al-yaumiyyah practiced by the masyayikh of Pesantren Annuqayah Guluk-Guluk Sumenep, and second, does the al-a'māl al-yaumiyyah masyayikh Annuqayah have a sanad connection with Islamic boarding schools in the nusantara. Data was collected by interviewing kiai of Annuqayah and related subjects and collecting documents related to their al-a'māl al-yaumiyyah references. The data is seen in the paradigm of sanad theory outside of hadith scholarship, to trace the continuity of sanad al-a'māl al-yaumiyyah masyayikh Annuqayah.There are two conclusions found. First, al-a'māl al-yaumiyyah masyayikh Annuqayah refers to the book al-A'māl al-Yaumiyyah al-Mukammalah published by Pesantren Annuqayah Lubangsa which collects al-a'māl al-yaumiyyah of Kiai Muhammad Ilyas bin Muhammad Syarqawi. Second, sanad al-a'māl al-yaumiyyah masyayikh Annuqayah is not connected with pesantren in the nusantara, but with Habib Tohir bin Husein bin Tohir, a scholar from Hadramaut, Yemen.